2013
DOI: 10.1007/s40262-013-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacokinetic–Pharmacodynamic Correlations of Therapeutic Peptides

Abstract: Peptides, defined as polymers of less than 50 amino acids with a molecular weight of less than 10 kDa, represent a fast-growing class of new therapeutics which has unique pharmacokinetic characteristics compared to large proteins or small molecule drugs. Unmodified peptides usually undergo extensive proteolytic cleavage, resulting in short plasma half-lives. As a result of their low permeability and susceptibility to catabolic degradation, therapeutic peptides usually have very limited oral bioavailability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
229
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(248 citation statements)
references
References 87 publications
5
229
0
Order By: Relevance
“…This is in keeping with animal studies that have isolated protein adducts and found them to generally range from about 50,000 to more than 100,000 Da [14]. Such high molecular weight proteins do not undergo significant glomerular filtration or other forms of renal clearance [15]. Furthermore, 68 % of 557 urine samples contained no quantifiable APAP-CYS, even when serum adduct concentrations were as high as 16.99 μM (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…This is in keeping with animal studies that have isolated protein adducts and found them to generally range from about 50,000 to more than 100,000 Da [14]. Such high molecular weight proteins do not undergo significant glomerular filtration or other forms of renal clearance [15]. Furthermore, 68 % of 557 urine samples contained no quantifiable APAP-CYS, even when serum adduct concentrations were as high as 16.99 μM (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…More recently, we have documented that RERF prevents both uPAR 88-92 -and VEGF-induced angiogenesis in vitro and in vivo (13). However, RERF is expected to have some pharmacokinetic drawbacks as drug candidate, which are common to peptides: they are usually very susceptible to proteolytic degradation in vivo and are rapidly cleared from the circulation in minutes (36). To overcome these drawbacks, we have generated a series of peptide analogues of RERF containing Ca-methyl-a-amino acids, a structural modification used in the past to overcome these limitations (37).…”
Section: Discussionmentioning
confidence: 99%
“…C yclic, stapled, and branched peptides constitute a unique and growing class of biomolecules with promise as therapeutics because of their biostability and resistance to proteolytic digestion in physiological environments [1][2][3][4][5][6][7]. In the context of therapeutics, peptide-based drug candidates display both advantages and disadvantages in comparison to their small molecule counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides, while frequently less toxic than small molecules when administered intravenously and exhibiting higher selectivity for specific biological functions, do not traverse cell membranes with the ease that small molecules do and are prone to proteolytic degradation [8,9]. However, peptides that are protected from degradation via cyclization or stapling have been shown to exhibit high potency and low toxicity, resulting in more promising candidates for drug administration than their linear counterparts [3][4][5][6][7]. A myriad of nonlinear peptides are found naturally in plants, fungi, and bacteria as well as synthetic ones produced in the laboratory [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%